Earnings Management and Firm Performance Following Open‐Market Repurchases - GONG, GUOJIN; LOUIS, HENOCK; SUN, AMY X. (Journal of Finance, 2008)
ABSTRACT Both post‐repurchase abnormal returns and reported improvement in operating performance are driven, at least in part, by pre‐repurchase downward earnings management rather than genuine growth in profitability. The downward earnings management increases with both the percentage of the company that managers repurchase and CEO ownership. Pre‐repurchase abnormal accruals are also negatively associated with future performance, with the association driven mainly by those firms that report the largest income‐decreasing abnormal accruals. The study suggests that one reason firms experience post‐repurchase abnormal returns is that post‐repurchase realized earnings growth exceeds expectations formed on the basis of pre‐repurchase deflated earnings numbers.